2019
DOI: 10.1111/1440-1703.12025
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variations of soil silicon availability and biogenic silicon flux in a lowland tropical forest in Malaysia

Abstract: Tropical tree species differ widely in their silicon (Si) accumulation patterns, but the implications of such species differences for ecosystem Si flux remain unexplored. We analyzed how biogenic Si flux via leaf litter and soil Si availability in the upper soil vary spatially within a 2 ha area in a lowland Dipterocarp forest in Peninsular Malaysia. Silicon concentration per unit leaf dry mass of 86 dominant tree species in this plot ranged from 0.4 to 126 mg/g. Soil Si availability at 100 sampling points and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 57 publications
(79 reference statements)
6
24
0
Order By: Relevance
“…5) (Zemunik et al 2015), and other species might benefit from the carboxylate exudation of their neighbours (Lambers et al 2018). This mechanism may also explain why we observed species with some of the highest leaf [Si] found in literature (up to 43 g kg −1 DW for Mesomelaena pseudostygia at stage 4) (Schoelynck et al 2010;Carey et al 2017Carey et al , 2019Schaller et al 2018;Ishizawa et al 2019;Nakamura et al 2019), despite Jurien Bay soils being among the most desilicated worldwide, with one of the lowest Si availability for plants (de Tombeur et al 2020b).…”
Section: Convergence Towards Silica-based Defences During Ecosystem Retrogressionsupporting
confidence: 58%
See 1 more Smart Citation
“…5) (Zemunik et al 2015), and other species might benefit from the carboxylate exudation of their neighbours (Lambers et al 2018). This mechanism may also explain why we observed species with some of the highest leaf [Si] found in literature (up to 43 g kg −1 DW for Mesomelaena pseudostygia at stage 4) (Schoelynck et al 2010;Carey et al 2017Carey et al , 2019Schaller et al 2018;Ishizawa et al 2019;Nakamura et al 2019), despite Jurien Bay soils being among the most desilicated worldwide, with one of the lowest Si availability for plants (de Tombeur et al 2020b).…”
Section: Convergence Towards Silica-based Defences During Ecosystem Retrogressionsupporting
confidence: 58%
“…2018; Ishizawa et al . 2019; Nakamura et al . 2019), despite Jurien Bay soils being among the most desilicated worldwide, with one of the lowest Si availability for plants (de Tombeur et al .…”
Section: Discussionmentioning
confidence: 99%
“…About 20% of the studied forb species can be classified as high-accumulating species (foliar Si > 5 mg g −1 ) and contributed most to the observed interspecific variation in foliar Si concentrations. Previous studies showed similar skewed distributions of Si concentration in dicots, with few high-accumulating and many lowaccumulating species (Schaller et al 2018;Ishizawa et al 2019;Hodson et al 2005;Deshmukh et al 2020). Physiological and ecological benefits of Si in alleviating abiotic and biotic stress, which were initially found in monocots and more recently in dicots (reviewed in Cooke and Leishman 2016;Putra et al 2020), are assumed to be especially pronounced in high accumulators (Ma 2004).…”
Section: Temperate Forbs Differ Considerably In Foliar Si Concentrationsmentioning
confidence: 83%
“…Si cycling ultimately primarily depends on the parent material in terms of mineral composition, with every mineral exhibiting different Si dissolution rates affecting Si availability [ 103 ]. The Si availability of soils is highly heterogenic at the landscape level [ 232 ], which might be due to hydrological effects. However, only a few articles show a larger dataset for Si availability in soils.…”
Section: Human Impacts and Global Change Effects On Soil Si Cyclinmentioning
confidence: 99%
“…ability [103]. The Si availability of soils is highly heterogenic at the landscape level [232], which might be due to hydrological effects. However, only a few articles show a larger dataset for Si availability in soils.…”
Section: Human Impacts and Global Change Effects On Soil Si Cycling 6mentioning
confidence: 99%